2014
DOI: 10.3389/fphys.2014.00017
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin7A promotes tumor growth and exerts a pro-angiogenic effect in macrophages of mammary tumor-bearing mice

Abstract: Semaphorins are a large family of molecules involved in axonal guidance during the development of the nervous system and have been recently shown to have both angiogenic and anti-angiogenic properties. Specifically, semaphorin 7A (SEMA7A) has been reported to have a chemotactic activity in neurogenesis and to be an immune modulator through α1β1integrins. SEMA7A has been shown to promote monocyte chemotaxis and induce them to produce proinflammatory mediators. In this study we explored the role of SEMA7A in a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
39
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 52 publications
0
39
0
1
Order By: Relevance
“…We and others have demonstrated that SEMA7A activates ERK signals via integrin β1 (ITGB1) in neurons and macrophages (15,19,20). Several studies using mice or human samples demonstrated that SEMA7A expression promotes mammary tumor progression, epithelial-to-mesenchymal transition (EMT), and angiogenesis (21)(22)(23)(24). Moreover, SEMA7A promotes cell growth in oral squamous carcinoma (25), activates tumor-associated macrophages in melanoma (26), and correlates with invasiveness of a glioblastoma cell line (27).…”
Section: Introductionmentioning
confidence: 99%
“…We and others have demonstrated that SEMA7A activates ERK signals via integrin β1 (ITGB1) in neurons and macrophages (15,19,20). Several studies using mice or human samples demonstrated that SEMA7A expression promotes mammary tumor progression, epithelial-to-mesenchymal transition (EMT), and angiogenesis (21)(22)(23)(24). Moreover, SEMA7A promotes cell growth in oral squamous carcinoma (25), activates tumor-associated macrophages in melanoma (26), and correlates with invasiveness of a glioblastoma cell line (27).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Sema7A has been shown to function as a regulator of the T-cell immune response by its effects on T-cell proliferation [16]. Notably, Sema7A has been demonstrated to have a clear effect on the migration processes of osteoblasts and osteoclasts in bone remodeling and a distinct role in tumor angiogenesis [17, 18]. Neovascularization, immunologic abnormality, and bone erosion all have crucial roles in the progression of RA [19, 20], suggesting that Sema7A may aggravate RA.…”
Section: Introductionmentioning
confidence: 99%
“…260 In metastatic melanomas, sema7A was reported to contribute to the metastasis of melanoma cells to lungs 261 and to function as a pro-angiogenic factor. 262 Likewise, it was reported to contribute to the metastasis of breast cancer cells by promoting epithelial to mesenchymal transition. 263 Recently, sema7A was found to be upregulated in oral squamous cell carcinoma, to promote their proliferation of these tumor cells, and to enhance their invasiveness.…”
mentioning
confidence: 99%